Fresh Supply Chain Coordination Considering Preservation Efforts and Freshness - Shuiwang Zhang, Min Zhang (Forest Chemicals Review, 2022)
A two-level fresh supply chain is composed of a single fresh product supplier and a single retailer, in which the supplier is responsible for transporting the product to the retailer. The fresh-keeping efforts of the supplier and the transportation time influence the freshness of the product. Simultaneously, the market demand of the product is related to its freshness and the market price. Given the perishable and vulnerable characteristics of fresh products, this paper introduces freshness, preservation effort level, preservation effort cost, and other factors to construct centralized and decentralized decision-making models and propose two pricing contracts to study the coordination of the fresh supply chain. The results indicate that adopting a two-part pricing contract can effectively improve the total profit of the supply chain, realize the Pareto improvement of the profit of the supply chain members, and stimulate the growth of fresh product market demand. There are five main conclusions: (1) The rational use of a two-part pricing contract can improve the total profit of the supply chain, which is closer to the centralized decision, and can realize Pareto improvement of supplier and retailer profit. (2) Using an appropriate two-part pricing contract by supply chain members can effectively improve the adverse impact of large fresh-keeping effort cost coefficient on the total profit of the supply chain under the lack of significant fresh-keeping technology advantage in the fresh supply chain. (3) Reasonable adoption of a two-part pricing contract by supply chain members can improve product market demand, increase the order quantity by suppliers, face retailers a larger market, and achieve a win-win situation. (4) The effect of cold chain service adopted by suppliers is not apparent when fresh products are sensitive to transportation time, while transportation time should be shortened to improve product freshness. (5) When the product is sensitive to the preservation effort level, the supplier can increase the investment in the preservation effort to improve the product’s freshness to stimulate the profit growth of the supply chain. However, this paper only considers the factors associated with suppliers and retailers in the supply chain without considering customer satisfaction. Future research can improve preservation efforts, product freshness, and customer satisfaction.